Studies on essential oil and antibacterial activities from Elettariopsis smithiae aff. Kam. - Anita’, H.; Mustafa, A.M.; Ibrahim’, H. (Malaysian Journal of Science, 2000)
The essential oil from Elettariopsis smithiae was prepared from fresh leaves, rhizomes and roots and the chemical components were determined by GC-MS. The main component of the root and rhizome was cis-p-ocimene. More than 20 compounds were detected from the leaves and the major components were found to be farnesal (28.62%) and cis, trans-farnesal (20.63%).